2012
DOI: 10.1097/mjt.0b013e3181e70d20
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Multidrug Resistant Advanced Alveolar Soft Part Sarcoma With Sunitinib

Abstract: Sunitinib is a tyrosine kinase/angiogenesis inhibitor with proven efficacy in gastrointestinal stromal tumor and advanced renal cell carcinoma. We are presenting the case report of a patient with aggressive alveolar soft part sarcoma with lung and bone metastases, who had failed multiple chemotherapy regimens showing significant response to sunitinib. There was not only complete regression of the primary tumor, stabilization of his bone metastases and significant improvement in the quality of life. Our report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Therefore, due to the pathophysiology and vascular nature of this tumor, novel therapeutic agents such as tyrosine kinase receptor inhibitors or antiangiogenic therapy are considered a rational approach for this disease . Recently, agents such as cediranib, sunitinib, dasatinib, pazopanib, and tivantinib have been used in ASPS with promising results. In Table , we summarize the results of reports regarding targeted therapy for ASPS including the current series .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to the pathophysiology and vascular nature of this tumor, novel therapeutic agents such as tyrosine kinase receptor inhibitors or antiangiogenic therapy are considered a rational approach for this disease . Recently, agents such as cediranib, sunitinib, dasatinib, pazopanib, and tivantinib have been used in ASPS with promising results. In Table , we summarize the results of reports regarding targeted therapy for ASPS including the current series .…”
Section: Discussionmentioning
confidence: 99%
“…One out of 14 patients with grossly resected tumour at diagnosis (IRS-I or II) treated with chemotherapy had a metastatic relapse versus 3 out of 14 who did not receive any adjuvant chemotherapy. Other drugs in ASPS may have an anti-angiogenesis effect, such as bevacizumab [9], sunitinib [10][11][12] or interferon alpha-2b [20]. Phase II trials with cediranib and a c-Met inhibitor (ARQ-197) have recently confirmed the efficacy of these drugs [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…Results. Median age was 13 years [range: [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Primary sites included mostly limbs (63%).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have recently reported responses in MiT tumors treated with multitargeted kinase inhibitors that block vascular endothelial growth factor receptor 2 (VEGFR2). Decreases in tumor dimensions and/or density were reported in ASPS and CCS treated with sunitinib37‐40 or cediranib 41. Moreover, minor responses have been reported in a patient with ASPS treated with bevacizumab,42 and both sunitinib and sorafenib have been reported to have activity in patients with tRCC 43, 44.…”
Section: Discussionmentioning
confidence: 96%